Synthesis and Antibacterial Activity of Zn(II) Schiff Base Complexes Derived from 3-Acetyl-2H-chromen-2-one - Hussain, Habib; Rubina Gilani, Syeda; Jabeen, Farkhanda; Ali, Zulfiqar; Rehman, Hajira; Hussain, Imdad (Asian Journal of Chemistry, 2015)
Zn(II) Schiff base complexes viz., bis[(E)-3-(1-(p-tolylimino)ethyl)-2H-chromen-2-one]zinc(II), bis[(E)-3-(1-((4-chlorophenyl)-imino)ethyl)-2H-chromen-2-one]zinc(II) and bis[(E)-3-(1-((2- nitrophenyl)imino)-ethyl)-2H-chromen-2-one]zinc(II) derived from 3-acetyl-2H-chromen-2-one and p-toluidine, p-chloro aniline and 2-nitroaniline, respectively, have been synthesized and characterized. Physical properties like, infrared spectroscopy and lmax are recorded and presence of metal is confirmed by atomic absorption spectroscopy. Infrared spectra reveal complex formation of Zn(II) with synthesized ligands. Both free Schiff bases and their Zn(II) complexes have been screened for antibacterial activity against Gram-positive Bacillus subtilis, Staphylococcus aureus, Methicillin-resistant Staphylococcus aureus (MRSA) and Gram-negative E. coli, P. aeruginosa, S. typhi by Agar plate diffusion method. All Schiff bases and their metal complexes appeared promising as antibacterial agents. Minimum inhibition concentrations were determined for each bacterial strain.